ANALISIS PEMILIHAN SUPPLIER TOU DI PT FLEXTRONICS TECHNOLOGY INDONESIA - Ria Esnidar Nainggolan; Ganda Sirait (LPPM Universitas Putera Batam, 2025)
The manufacturing industry's growing competition demands efficient supply chain management to maintain a competitive edge. An integrated supply chain reduces costs, removes barriers, and ensures fast, accurate product distribution. Supplier relationships and adherence to Supplier Terms of Use (TOU) are crucial for optimization.This study focuses on supplier selection for PT Flextronics Technology Indonesia, a Batam-based semiconductor manufacturer established in 1991. As a key player in the global semiconductor supply chain, the company supports industries like electronics and industrial equipment.Using the Analytical Hierarchy Process (AHP), the research prioritizes supplier selection criteria: Accuracy, Delivery Accuracy, Flexibility, Cost, and Responsibility. AHP results show Oshiba Technology Sdn Bhd as the top supplier with a 28% priority score, followed by Flextronics International Ireland Ltd at 21%. Meanwhile, TOPSIS evaluates supplier performance, identifying Flextronics International Ireland Ltd as the closest to the ideal solution (0.651).The findings highlight that while Oshiba ranks highest in strategic priority, Flextronics International Ireland Ltd excels in operational performance, reflecting alignment between qualitative and quantitative assessments.